A mutation in P23, the first gene in the RNA polymerase sigma A (sigma 43) operon, affects sporulation in Bacillus subtilis. - Zuberi, A R (1990)
Mutations within P23, the first gene of the Bacillus subtilis sigma A operon, were not detrimental to vegetative growth or sporulation. One deletion of P23 resulted in a strain that sporulated earlier than the wild type. This aberrant phenotype may be due to the simultaneous deletion of a sigma H promoter from the sigma A operon.